Pengaruh Budaya Organisasi dan Etika Kerja Islami Terhadap Kinerja Pegawai pada Kementrian Agama Kota Binjai - Ridho Raditya Kurniawan Ritonga; Nur Rahmah Amini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
So that members of the organization can focus and pay maximum attention to the values applied when managing the organization at the Ministry of Religion of Binjai. Next, this research analyzes and determines the influence of organizational culture on employee performance, then analyzes and determines the influence of Islamic work ethics on employee performance, and analyzes and determines the influence of organizational culture and Islamic work ethics simultaneously on employee performance . The aim of this research is to simultaneously analyze the influence of employee performance on employee performance. The type of research used was quantitative with a survey method and a sample of 39 people. The data used is primary data obtained through distributing questionnaires which were distributed directly and answered by employees of the Ministry of Religion of Binjai City.